Crispin : the cross of lead - Avi, 1937- (New York : Hyperion Books For Children, 2004)
Falsely accused of theft and murder, an orphaned peasant boy in fourteenth-century England flees his village and meets a larger-than-life juggler who holds a dangerous secret.
Sequel: Crispin, at the edge of the world.
G5
Keywords: Identity -- Fiction; Orphans -- Fiction; Middle Ages -- Fiction; Great Britain -- History -- Edward III, 1327-1377 -- Fiction